An Empirical Investigation of Efficiency and Price Uniformity in Competing Auctions - Tommy Andersson; Christer Andersson; Fredrik N. G. Andersson (Lund University, School of Economics and Management, Department of Economics, 2010)
This paper investigates empirically a number of hypotheses that are related to efficiency and price uniformity in online competing auctions for train tickets. The data set is ideal for analyzing competing auctions since each ticket is sold in a separate auction and all auctions with identical tickets starts and ends at exactly the same time. The results unambiguously demonstrate that there is a strong relationship between efficiency and price uniformity on the one hand and the number of submitted cross-bids on the other hand. These findings are in line with what theory suggests.
Keywords: D40; D44; 330; Competing auctions; Cross-bidding; Efficiency; Price uniformity